DHHC7 Palmitoylates Glucose Transporter 4 (Glut4) and Regulates Glut4 Membrane Translocation - Du, Keyong (J Biol Chem, 2017)
Insulin-dependent translocation of glucose transporter 4 (Glut4) to the plasma membrane plays a key role in the dynamic regulation of glucose homeostasis. We recently showed that this process is critically dependent on palmitoylation of Glut4 at Cys-223. To gain further insights into the regulation of Glut4 palmitoylation, we set out to identify the palmitoyl acyltransferase (PAT) involved. Here we report that among 23 mammalian DHHC proteins, DHHC7 is the major Glut4 PAT, based on evidence that ectopic expression of DHHC7 increased Glut4 palmitoylation, whereas DHHC7 knockdown in 3T3-L1 adipocytes and DHHC7 KO in adipose tissue and muscle decreased Glut4 palmitoylation. Moreover, inactivation of DHHC7 suppressed insulin-dependent Glut4 membrane translocation in both 3T3-L1 adipocytes and primary adipocytes. Finally, DHHC7 KO mice developed hyperglycemia and glucose intolerance, thereby confirming that DHHC7 represents the principal PAT for Glut4 and that this mechanism is essential for insulin-regulated glucose homeostasis.